Upaya Meningkatkan Kemampuan Literasi Dan Numerasi Pada Anak Melalui Bimbingan Belajar Di Desa Sawoo Kabupaten Ponorogo - Kenlies Era Rosalina Marsudi; Ade Ayu Irawati; Dwi Nurhidayati; Tinda Mai Saputri (Pakis Journal Institute, 2024)
The free tutoring community service activity at the Al-Mutaqqin Prayer Room in Sawoo Village was carried out because so far there has never been a single non-formal tutoring program in the Sawoo Village area. Elementary school age children only study formally at school and some of them get additional education through independent study at home with parental guidance. This activity aims to explore students' abilities to improve literacy and numeracy to make it even better. Participants in this tutoring service activity are all students from grade 1 to grade 6 of elementary school. Tutoring was carried out in order to familiarize and also improve literacy and numeracy learning abilities for children in the environment around Sawoo Village. The implementation of the activity was carried out in 3 stages. First, make an activity plan by first observing students' literacy and numeracy skills. Second, the implementation takes the form of free tutoring which is held 4 times a week with a duration of 1 hour 30 minutes. Third, evaluate and monitor activities that have been carried out. The results obtained from this free tutoring activity are an increase in students' abilities in the areas of literacy and numeracy, students are also able to solve problems in the context of daily life and are able to follow and understand the material taught in this tutoring process well.